Development of Computerized Nursing Care Plans in the Ambulatory Setting - Wright, Cynthia A. (1988)
This paper presents the development and use of computerized nursing care plans in the ambulatory setting of an Internal medicine residency program where resident physicians are the primary providers. Using a COSTAR-based system, a standard set of nursing diagnosis statements was used as a basis for developing the appropriate forms to capture data. This has led to better communication between resident physician and nurse, and the development of computerized nursing audits to improve quality of care in the Ambulatory Medicine Center (AMC). A discussion of the design and use of nursing care plans as they are used in the AMC is included.